PERENCANAAN UNIT PRE-TREATMENT AIR LIMBAH INDUSTRI SPARE PART KENDARAAN BERMOTOR - Setiyono, Setiyono (Center for Environmental Technology, 2014)
PT. Shei Tai Industrial, is one of the industries that produce motor vehicle spare parts such as the engine block. With these production activities, PT. Shei Tai Industrial will result in the production of domestic waste and waste that contains oil and chemicals (solvents) with a high enough concentration. The high levels of pollutant waste PT. Shei Tai Industrial, resulting in the waste industry cannot be accepted directly into the WWTP area, so PT. Shei Tai Industrial obliged to make a pre-treatment unit prior to the WWTP effluent channel region. For pre-treatment planning unit, PT. Shei Tai Industrial has teamed up with researchers from the Center for Environmental Technology to make planning pre-treatment unit design. This unit is planned by using physical-chemical process technology.Ã‚Â Keywords: Waste Industry, Design of wastewater pre-treatment.